First-principles investigation on the brittleness mechanism of TiAl alloys and the effect of doping - Zewen Zhang; Qinghua Song; Yapeng Li; Kunyu Li; Jing Qin; Zhanqiang Liu (Journal of Materials Research and Technology)
TiAl alloys are widely used in aerospace applications due to their excellent performance and lightweight characteristics. However, their intrinsic brittleness has somewhat limited their further development. In this study, first-principles calculations are performed on TiAl alloys and their compounds. The elastic properties of the structure-optimized materials are computed, and the single-crystal and polycrystalline elastic constants are obtained to explain the intrinsic brittleness mechanism of TiAl alloys. Various concentrations of elemental doping are employed to optimize the performance of the alloys. A comparative analysis of the mechanical properties, electronic structure, and thermodynamic properties is conducted based on the computational results. The findings reveal that, while elemental doping reduces the hardness of the material to some extent, it significantly improves its ductility and machinability by reducing the directional strength of the covalent bonds in TiAl alloys. This provides theoretical guidance for advancing the development of TiAl alloys.